1998
DOI: 10.1046/j.1523-1755.1998.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interactions between inducible nitric oxide synthase and eicosanoids in glomerular immune injury

Abstract: In a rat model of glomerular immune injury induced by administration of anti-glomerular basement membrane antibody and resembling human rapidly progressive glomerulonephritis, we explored whether activation of inducible nitric oxide synthase (iNOS) regulates synthesis of eicosanoids originating from cyclooxygenation or lipoxygenation of arachidonic acid. At early stages (24 hr) of injury, inhibition of iNOS using the selective inhibitor L-N6-(1-iminoethyl) lysine (L-NIL) at doses sufficient to reduce urinary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…As an alternative mechanism, activation of PPAR could enhance cytokine-elicited iNOS induction by promoting the degradation of lipidic negative modulators, among which could be some COX products, including PG of the J series, like 15d-PGJ 2 . In fact, inhibition of COX activity has been reported to lead to enhanced iNOS expression in a model of immune glomerulonephritis (49). At this point, however, our results do not support the involvement of PPAR in the effects herein described.…”
Section: Discussioncontrasting
confidence: 92%
“…As an alternative mechanism, activation of PPAR could enhance cytokine-elicited iNOS induction by promoting the degradation of lipidic negative modulators, among which could be some COX products, including PG of the J series, like 15d-PGJ 2 . In fact, inhibition of COX activity has been reported to lead to enhanced iNOS expression in a model of immune glomerulonephritis (49). At this point, however, our results do not support the involvement of PPAR in the effects herein described.…”
Section: Discussioncontrasting
confidence: 92%
“…Neuronal NOS (nNOS) is primarily found at the macula densa where it is a physiologic component of the tubuloglomerular feedback loop and regulates the tone of afferent arteriole via production of nitric oxide [24]. The inducible NOS isoform (iNOS) is not expressed in normal rat glomeruli [4,25] which primarily express the constitutive NOS isoforms are more abundant than that of iNOS [26,27]. Normal rat glomeruli and cultured glomerular cells also produce O 2 − at baseline and in response to inflammatory mediators [1][2][3]28].…”
Section: Discussionmentioning
confidence: 99%
“…NO has been identified in models of immune renal injury [13, 14, 15]. Furusu et al [16]have shown that the immunohistochemical localization of iNOS in human glomerulonephritis increases during disease, whereas eNOS staining decreases as compared with biopsy specimens from healthy individuals.…”
Section: No In the Glomerulonephritic Kidneymentioning
confidence: 99%
“…N G -nitro- L -arginine methyl ester treatment reduced macrophage infiltration and resulted in significant increases in eNOS [13]. Lianos et al [15]have reported worsening of proteinuria in glomerulonephritic rats treated with the specific iNOS inhibitor L -N 6 -(1-iminoethyl)lysine ( L -NIL).…”
Section: No In the Glomerulonephritic Kidneymentioning
confidence: 99%